Visualisasi Data Program Vaksinasi Covid-19 di Kota Depok dengan Big Data Analytics - Rizki Elisa Nalawati; Dewi Yanti Liliana (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Indonesia and various country in the world are facing the problem of the Covid-19 pandemic. In Indonesia, the suspect Covid-19 was found in March 2020 in Depok City, West Java. Until February 2021, the number of positive COVID patients was 1,527,524. The need for supervision of the administration of vaccines is carried out by the Depok City Health Office on a number of health facilities that are trusted to administer vaccines to the public. This supervision is carried out using surveillance through visualization of vaccine administration data from the community. So far, the number of vaccines given to all health facilities in Depok City from January to August is around 613276 times which includes the administration of dose 1, dose 2 and dose 3. The amount of existing data can be managed and visualized properly using big data analytics. To get a good shape and visualization in decision making, several data cleansing processes are carried out up to the visualization stage. The use of big data analytics can be used to visualize descriptive data that is able to describe the rhythm of vaccination in Depok City, categorization of vaccine recipients, the type of vaccine given to the number of doses given. So it can be estimated that every month, vaccine recipients will continue to increase, both receiving dose 1, dose 2 and dose 3. This is in line with the Depok government's target which will complete the provision of vaccines to the people of Depok by the end of 2021